GeoFlorida 2010 2010
DOI: 10.1061/41095(365)241
|View full text |Cite
|
Sign up to set email alerts
|

The Behaviour of Ballasted Track Foundations: Track Drainage and Geosynthetic Reinforcement

Abstract: Ballasted Rail tracks are widely used throughout the world due to its resiliency to the repeated wheel loads, low construction cost and ease of maintenance. However, the ballast layer needs periodic maintenance due to its deformation and degradation associated with particle breakage and fouling. A proper understanding of the contamination due to various types of fines and its implications on track drainage is a pre-requisite for effective implementation of track maintenance operations. A new parameter Void Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 3 publications
1
23
0
Order By: Relevance
“…Another solution widely investigated and applied over the past few decades is the use of geosynthetics, which by decreasing both vertical and lateral deformation can increase intervals between maintenance operations [8][9][10][11]. Within the same family are considered polyurethane-based techniques, which provide (when cured) a 3D reinforcement similar to geocells [12].…”
Section: Background Of the Problem And State Of The Artmentioning
confidence: 99%
“…Another solution widely investigated and applied over the past few decades is the use of geosynthetics, which by decreasing both vertical and lateral deformation can increase intervals between maintenance operations [8][9][10][11]. Within the same family are considered polyurethane-based techniques, which provide (when cured) a 3D reinforcement similar to geocells [12].…”
Section: Background Of the Problem And State Of The Artmentioning
confidence: 99%
“…Finite element modelling of rail track structure is essentially a 2D problem because in reality, the longitudinal deformation of a long straight section of track section (i.e., perpendicular to the sleepers) are generally very small, thus ensuring plane-strain conditions [11][12][13][14]35]. In this paper a higher order constitutive model and interface elements were used to capture the real behaviour of the track.…”
Section: Finite Element Modellingmentioning
confidence: 99%
“…Recently, Indraratna et al [35] defined a new parameter, the Void Contaminant Index (VCI), which is expressed as:…”
Section: Assessment Of Ballast Foulingmentioning
confidence: 99%
“…Ballast was collected from Bombo quarry, New South Wales, Australia, then cleaned and sieved according to Australia Standards (AS 2758(AS .7, 1996. Coal fines were used as fouling contaminant and the Void Contamination Index (VCI) introduced earlier by (Indraratna et al 2010) was applied to measure the degree of fouling, as shown:…”
Section: Introductionmentioning
confidence: 99%